Comparative analysis of old people practicing physical exercises and sedentary ones regarding the risk of falling - Priscila Gularte Padoin; Marisa Pereira Gonçalves; Talitha Comaru; Antônio Marcos Vargas da Silva (O Mundo da Saúde, 2010)
Postural instability with occurrence of falls is a characteristic of aging, representing a reason of worry for old people, because it can cause physical incapacity and loss of independence. The objective of this study was to evaluate the risk of falls of old women practicing physical exercises and sedentary ones. Women more than 60 years old, both active and sedentary were tested regarding the risk of falling using Timed Up and Go, Berg Scale and Performance Oriented Mobility Assessment. The following results were obtained: the group of active women had better performances in tests Timed Up And Go (p = 0.001), Scale of Berg (p = 0.002)) and Performance Oriented Mobility Assessment (p = 0.002) than women of the sedentary group. The story of pain in the feet and fear of falling was greater in the group of sedentary women. One thus concluded that sedentary women presented less functional mobility and more balance deficits, as well as alterations in marching when compared to those which practiced physical exercise regularly. We conclude that the practice of physical exercises contributed to reducing the risk of falls in the studied group.